Penerapan Manajemen Risiko Kecelakaan Kerja pada Proyek Penggantian Jembatan Tukad Ayung Denpasar, Bali - I Wayan Muka (Jurnal Syntax Admiration, 2024)
Management of occupational accident risk involves systematic, planned, structured, and comprehensive efforts to mitigate the factors that contribute to the occurrence of work accidents. This study aims to examine the risk of work accidents in the Tukad Ayung Bridge replacement project, especially at the stage of installing concrete girders. Qualitative and quantitative data from primary and secondary sources were used, collected through observation, interviews, questionnaires, literature review, and documentation analysis. The Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method is used for data analysis. The findings revealed 24 types of work accident risks at seven stages of concrete block installation in the project including the concrete girder preparation stage, girder truss making, erection (setting segmental girder), prestressed steel installation (strand), cabel strand stressing work, concrete girder tendon grouting, and diaphragm installation stage. The results of the risk analysis on the concrete girder installation work on the Tukad Ayung Bridge replacement project, are in the moderate category, which is as many as 12 risks. Furthermore, as many as 11 risks are included in the high category. Meanwhile, in the extreme category as much as 1 risk.